Anxiogenic drug administration and elevated plus-maze exposure in rats activate populations of relaxin-3 neurons in the nucleus incertus and serotonergic neurons in the dorsal raphe nucleus. (10th September 2015) - Lawther, A.J.; Clissold, M.L.; Ma, S.; Kent, S.; Lowry, C.A.; Gundlach, A.L.; Hale, M.W.
Highlights: Anxiogenic stimuli activate serotonergic neurons in the dorsal raphe nucleus and relaxin-3 neurons in the nucleus incertus. Activation of relaxin-3 neurons in the nucleus incertus is associated with changes in anxiety-like behavior. These findings support a role for the interaction of relaxin-3 and serotonergic systems in the control of anxiety. Abstract: Anxiety is a complex and adaptive emotional state controlled by a distributed and interconnected network of brain regions, and disruption of these networks is thought to give rise to the behavioral symptoms associated with anxiety disorders in humans. The dorsal raphe nucleus (DR), which contains the majority of forebrain-projecting serotonergic neurons, is implicated in the control of anxiety states and anxiety-related behavior via neuromodulatory effects on these networks. Relaxin-3 is the native neuropeptide ligand for the Gi/o -protein-coupled receptor, RXFP3, and is primarily expressed in the nucleus incertus (NI), a tegmental region immediately caudal to the DR. RXFP3 activation has been shown to modulate anxiety-related behavior in rodents, and RXFP3 mRNA is expressed in the DR. In this study, we examined the response of relaxin-3-containing neurons in the NI and serotonergic neurons in the DR following pharmacologically induced anxiety and exposure to an aversive environment. We administered the anxiogenic drug FG-7142 or vehicle to adult male Wistar rats and, 30 min later, exposed them to either the elevated plus-maze or home cage control conditions. Immunohistochemical detection of c-Fos was used to determine activation of serotonergic neurons in the DR and relaxin-3 neurons in the NI, measured 2 h following drug injection. Analysis revealed that FG-7142 administration and exposure to the elevated plus-maze are both associated with an increase in c-Fos expression in relaxin-3-containing neurons in the NI and in serotonergic neurons in dorsal and ventrolateral regions of the DR. These data are consistent with the hypothesis that relaxin-3 systems in the NI and serotonin systems in the DR interact to form part of a network involved in the control of anxiety-related behavior.